Seed Priming: Tool towards Sustainable Agriculture - VIDYA CJ; N NETHRA; N NETHRA; N NETHRA (Seed Research, 2026)
Seed germination stands as a pivotal and intricate physiological occurrence in the life cycle of plants, frequently susceptible to environmental and biological stressors culminating in unpredictable germination patterns. Priming, a time-honoured technique traditionally employed for ensuring synchronized seedling growth and a steadfast crop stand, has evolved into a formidable instrument for promoting sustainable agriculture in contemporary times. Its application extends to mitigating an array of abiotic stresses, encompassing salinity, drought, cold, and heavy metal stresses, concurrently fostering the robust growth of crop plants. Notably, priming has demonstrated efficacy against biotic stress agents, countering pathogenic bacteria and fungi. This exhaustive review seeks to encapsulate diverse, successful priming methodologies that have yielded commendable outcomes, spanning enhanced growth, augmented yield, bolstered disease resistance and heightened tolerance to both abiotic and biotic stresses. The exploration delves into the subcellular transformations induced by priming, elucidating the underlying molecular and physiological aspects. The specific proteomic changes during imbibition and seed dehydration processes associated with priming, contributing significantly to elevated seed vigour, are also meticulously summarized. Against the backdrop of escalating global demands for food supply, driven by an expanding population and the excessive application of chemical fertilizers compromising soil health, seed priming emerges as a prudent, cost-effective, and eco-friendly alternative. It presents a pragmatic approach to address the imperatives of global food security through sustainable agricultural innovation.